Corneal Endothelial Cell Changes with the Age in Normal Iraqi Population Using Em-3000 Tomey Speculer Microscope - Mohanad M. Hasan, Dr. (International Journal of Engineering and Technology, 2018)
"Background:Â The cornea consists of the following layers, each of which is critical to normal function: 1. Epithelium. 2. Bowman layer.Â Â Â 3. Stroma. 4. Descemnts membrane.Â Â Â 5. Endothelium.Â The corneal endothelium is composed of a single layer, mostly of hexagonal cells.Â Â Approximately 500,000 cells are present, with a density of about 3000 cells/mm2. The size, shape, and morphology of the endothelial cells can be observed by specular microscopy at the slit lamp"."Patients and methods: 400 eyes of 200 patients who attended the ophthalmology department in Al-Zahraa teaching hospital were included in the study. Patients were grouped into five groups according to age:Â Â [G1] less than 20 years. [G2] 20-30 years. [G3] 31-40 years.Â [G4] 41-50 years. [G5] more than 50 years so, we have five age groups.Patients with history of intraocular surgery or ocular trauma, increased intraocular pressure, uveitis, corneal opacity, evidence of endothelial dystrophy on slit-lamp bio microscopy, diabetes mellitus and contact lens wearer were excluded from the study. After routine ophthalmic examination, all patients underwent specular microscopy using a noncontact specular microscopy [EM-3000 tomey specular microscope]"."Results: The ECD of population 2718.34 Â± 320.38 cell/mm2 [range, 1551 to 3376)]. The Avg. /Âµm2 370.03Â± 46.99 [range, 232 to 566]. The C.V. 39.3 Â±7.66 [range, 25 to 73] and the hexagonal cell per cent 0.507 Â± 0.112 [range 0.00 to 0.91]. There were no statistically significant differences in ECD, Avg., C.V. and hexagonal cell per cent between right and left eyes [P= 0.846, P=0.951, P= 0.290, P= 0.419 respectively]. Also there were no statistically significant differences in ECD, Avg., C.V. and hexagonal cell per cent between genders [P= 0.483, P= 0.237, P= o.258 and P= 0.439 respectively]. There were a statistical significant decrease in ECD and hexagonal cell per cent with increase in the age [r= -0.84 and r= -0.72 respectively]. The rate of cell loss was 0.8% per year".Aim of the study:To evaluate the corneal endothelial layer changes in normal Iraqi population with age by using EM-3000 tomey specular microscope.Â Â Â